Penerapan Model Pembelajaran Kooperatif Tipe Team Games Tournament (TGT) di Kelas X SMAN 4 Kota Bengkulu - Safniyeti Safniyeti; Abas Abas; Aceng Ruyani (Biota, 2017)
Cooperative learning of Team Games Tournament (TGT) with numbered media card is one of teaching method that can be applied to biology. The objectives of this research were to describe the activities of teacher, activities of student student, and result student learning with apply cooperative learning model of Team Games Tournament (TGT). This was a classroom action research (CAR) with quantitative descriptive method and the subjects of this research were biology teachers and 34 students of SMAN 4 class XF Bengkulu city. The instrument used in this research was the observation and test sheets. Data collected were analyzed by calculating the average and specifies the range of values ​​for each criterion, while the test of data analyzed calculating the average value of the class and percentage of completeness classical learning. Results of data analysis observation of the teacher activity first cycle obtained to score of 34.5 with good criteria, then increased in the second cycle to 38 with good criteria. The activity of students in the first cycle obtained score of 34.5 with good criteria, then increased in the second cycle to 37 with good criteria. The student learning results the first cycle of 73.55% with incomplete criteria then increased in the second cycle to be 88.23% with complete criteria. This applied model of learning type TGT could upgrade the activities of teacher, activities of student, and the learning results of Biology students class XF SMAN 4 Bengkulu City. Keywords : Cooperative Learning, Team Games Tournament (TGT); Result of learning, Student activity; Teacher activity